The Use of Alternative Routes for the Delivery of Intra‐Arterial Chemotherapy for Retinoblastoma. Issue 5 (November 2020) - Sweid, Ahmad; Hammoud, Batoul; Texakalidis, Pavlos; Xu, Vivian; Shivashankar, Kavya; Baldassari, Michael P; Das, Somnath; Tjoumakaris, Stavropoula; Shields, Carol L; Ancona‐Lezama, David; Lim, Li‐Anne S; Dalvin, Lauren A; et al.
Abstract : BACKGROUND: : The introduction of intra‐arterial chemotherapy (IAC) for treatment of retinoblastoma considerably changed the paradigm by which this disease is managed, with event‐free survival rates being above 70%. OBJECTIVE: : To analyze efficacy of IAC treatment using alternative approaches to ophthalmic artery catheterization (OAC), such as external carotid artery approach or balloon‐assisted drug delivery. METHODS: : This is a retrospective chart review for subjects receiving IAC for retinoblastoma. The primary approach was OAC. In cases in which selective OAC was not feasible, alternative routes including catheterization of the external carotid artery or use of a balloon‐assisted drug infusion were used. RESULTS: : This study included 197 consecutive patients with 207 retinoblastomas who underwent 658 IAC procedures overall. The mean age at diagnosis was 24 mo, and 54.5% of the study population was male. Success rate with IAC was 97% (639). Alternative approaches to OAC were, in total, 42 cases (6.4%)—external carotid artery catheterization and use of ICA balloon were performed in 22 (3.3%) and 20 (3%) cases, respectively. A mean of 3.1 IAC cycles were performed for each patient. In total, there were 23 technical failures of the primary OAC technique (3.4%). Periprocedural adverse events occurred in 4 procedures (0.6%). Use of an alternative technique for chemotherapy delivery other than selective OAC in at least one IAC cycle was not a predictor of enucleation. CONCLUSION: : IAC is a safe and effective treatment option for retinoblastoma. Chemotherapy delivery using alternative techniques is as effective as selective OAC.